2016
DOI: 10.4049/jimmunol.1502146
|View full text |Cite
|
Sign up to set email alerts
|

LincRNA-Cox2 Promotes Late Inflammatory Gene Transcription in Macrophages through Modulating SWI/SNF-Mediated Chromatin Remodeling

Abstract: LincRNAs are long non-coding transcripts (>200 nt) from the intergenic regions of annotated protein-coding genes. One of the most highly induced lincRNAs in macrophages upon TLR ligation is lincRNA-Cox2, which has recently been shown to mediate both the activation and repression of distinct classes of immune genes in innate immune cells. We report here that lincRNA-Cox2 located at chromosome 1 proximal to the prostaglandin-endoperoxide synthase 2 (Ptgs2/Cox2) gene is an early-primary inflammatory gene controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
188
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 194 publications
(194 citation statements)
references
References 58 publications
5
188
1
Order By: Relevance
“…NF-kB signaling can regulate both the activation and inhibition of lncRNA expression (46,47). It was first described in 2013 in mouse bone marrow-derived dendritic cells that transcription of lncRNA genes in response to TLR signaling is activated in an NF-kB-dependent manner (26).…”
Section: Discussionmentioning
confidence: 99%
“…NF-kB signaling can regulate both the activation and inhibition of lncRNA expression (46,47). It was first described in 2013 in mouse bone marrow-derived dendritic cells that transcription of lncRNA genes in response to TLR signaling is activated in an NF-kB-dependent manner (26).…”
Section: Discussionmentioning
confidence: 99%
“…Arguably the best studied lncRNA that functions to modulate the inflammatory response is lincRNA-Cox2, which has been found to act as both an enhancer and a suppressor of inflammation in a gene-specific manner (18,22,26,57). After TLR4 activation and ensuing NF-B signaling, lincRNA-Cox2 was induced greater than 1000-fold in bone marrow-derived dendritic cells over the course of the following 12 h (22).…”
Section: Curious Case Of Lincrna-cox2mentioning
confidence: 99%
“…Analysis of the expression time course revealed that it is an early primary NF-B response gene, similar to Cxcl2 (18, 57). Func-tionally, silencing of lincRNA-Cox2 resulted in up-regulation of almost 800 genes and down-regulation of many other genes in non-stimulated cells (22,57), suggesting a role for lincRNACox2 in basal gene transcription. Many of these genes are inflammatory genes, including Ccl5, Cx3cl1, Ccrl, and IFNstimulated genes, including Irf7, Oas1a, Oas1l, Oas2, Ifi204, and Isg15.…”
Section: Curious Case Of Lincrna-cox2mentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that knocking out Pnky from stem cells can increase the output of neurons by three to four times, which implies that Pnky and other lncRNA will eventually play an important role in regenerative medicine and cancer treatment. More studies have focused on the lncRNA regulation of gene transcription [17,18], recent studies have shown that a new mechanism of lncRNA-Cox2 can regulate Il12B transcription, supporting lncRNA to play an important role in regulating the inflammatory response of intestinal epithelial cells [17], and lncRNA-Cox2 can mediate the activation and inhibition of different immune genes in innate immune cells [18]. In a word, the regulation of long noncoding RNA is being paid more and more attention.…”
Section: Modeling and Analysis Of Lncrnamentioning
confidence: 99%